2022
DOI: 10.1007/s12185-022-03493-8
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved versus fresh peripheral blood allogeneic stem cell transplantation outcomes in patients receiving post-transplant cyclophosphamide for graft-versus-host prophylaxis during the COVID-19 pandemic: a single center experience

Abstract: Background/objective Cryopreservation of grafts is not common practice in allogeneic hematopoietic stem cell transplant (HSCT) recipients. However, our center had to use cryopreserved cells for allogeneic HSCT during the COVID-19 pandemic to avoid delays in transplantation due to uncertainty regarding patient and donor exposures. Study designWe retrospectively evaluated post-transplant engraftment and survival outcomes of adult patients who received cryopreserved versus fresh allografts during the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Therefore, the authors concluded that the inferior outcomes of cryopreserved transplants were possibly due to the combination of ATG and PTCy impacting the differential tolerance to cryopreservation of various components of the grafts [ 100 ]. Similar findings were reported by Guo et al in a single center study involving 34 patients receiving cryopreserved PBSC transplant and 31 controls [ 101 ]. Conversely, various single-institution studies found no differences between cryo- and fresh grafts in unrelated donor transplants [ 102 , 103 , 104 , 105 , 106 ].…”
Section: Clinical Impact Of Allogenic Peripheral Blood Stem Cell Cryo...supporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, the authors concluded that the inferior outcomes of cryopreserved transplants were possibly due to the combination of ATG and PTCy impacting the differential tolerance to cryopreservation of various components of the grafts [ 100 ]. Similar findings were reported by Guo et al in a single center study involving 34 patients receiving cryopreserved PBSC transplant and 31 controls [ 101 ]. Conversely, various single-institution studies found no differences between cryo- and fresh grafts in unrelated donor transplants [ 102 , 103 , 104 , 105 , 106 ].…”
Section: Clinical Impact Of Allogenic Peripheral Blood Stem Cell Cryo...supporting
confidence: 90%
“…In total, 1739 references were identified on 15 January 2024. In the end, 29 papers were included [ 54 , 55 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ] ( Figure 1 ).…”
Section: Clinical Impact Of Allogenic Peripheral Blood Stem Cell Cryo...mentioning
confidence: 99%
See 3 more Smart Citations